2022
DOI: 10.1155/2022/7541378
|View full text |Cite
|
Sign up to set email alerts
|

Naloxegol to Prevent Constipation in ICU Adults Receiving Opioids: A Randomized Double-Blind Placebo-Controlled Pilot Trial

Abstract: Background. Constipation is frequent in critically ill adults receiving opioids. Naloxegol (N), a peripherally acting mu-receptor antagonist (PAMORA), may reduce constipation. The objective of this trial was to evaluate the efficacy and safety of N to prevent constipation in ICU adults receiving opioids. Methods and Patients. In this single-center, double-blind, randomized trial, adults admitted to a medical ICU receiving IV opioids (≥100 mcg fentanyl/day), and not having any of 17 exclusion criteria, were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The final selection included 9 papers: two randomized controlled trials, 19,20 one prospective case-series, 21 three retrospective case-series [22][23][24] and three case reports. [25][26][27] Tables 3 and 4 report the study characteristics and the main outcomes.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The final selection included 9 papers: two randomized controlled trials, 19,20 one prospective case-series, 21 three retrospective case-series [22][23][24] and three case reports. [25][26][27] Tables 3 and 4 report the study characteristics and the main outcomes.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Among the cohort studies, only Sawh et al found a clear benefit of Methylnaltrexone over conventional laxative therapy in terms of number of patients laxating within 24 h and hours to laxation. 22 The meta-analysis, instead, shows that both treatment with PAMORAs or non-PAMORAs drugs resulted in overlapping 19,20,23 In particular, both time to laxation and number of patients laxating at the shortest follow-up are similar between the two groups (Figure 1). The meta analysis only shows a trend, without statistical significance, toward a lower residual gastric volume in patients treated with PAMORAs (Figure 1, lower panel).…”
Section: Systematic Reviewmentioning
confidence: 99%
See 3 more Smart Citations